ROOT CANAL CONFIGURATION OF MAXILLARY FIRST PREMOLAR TEETH IN A SUBPOPULATION OF PESHAWAR USING TOOTH CROSS-SECTIONING METHOD; AN INVITRO STUDY - Khattak, Munawar Aziz; Faiza Ijaz; Nofil Ahmad; Sana Arbab; Imran Khattak; Khattak, Yusra Jamil (Journal of Ayub Medical College Abbottabad, 2022)
Background: Knowledge of tooth morphology is obligatory for achieving success in dental treatment. The root canal configuration of maxillary first premolar (MFP) has been shown to be highly varying. The study was conducted to assess the canal configurations in the roots of upper first premolars within a sample population of Peshawar with the help of tooth cross-sectioning method. Methods: The extracted 250 maxillary first premolars had undergone access cavity preparation after cleaning and pulp was removed from each individual tooth. The root canals were located in the pulp chamber floor and then India ink was injected in to their orifices. When the canals get stained the roots were cross-sectioned at three levels to assess the configurations of root canals using a categorization method devised by Weine. SPSS version 19 was used to analyze the data. A p-value of less than 0.05 was considered statistically significant. Results: Among 250 maxillary first premolars, the common root canal configuration was Weine’s type-IV in 30.4% and type-III in 30.0% teeth. Weine’s type-I and type-II were observed in 24.8% and 8.8% premolars, respectively. Variable root canal configurations were seen in 6.0% teeth. Apical delta was found in 1 (0.4%) tooth. A highly statistically significant difference was observed when root canal configuration was compared with external root morphology. Conclusion: Weine’s type-IV and type-III root canal configurations were frequently observed in maxillary first bicuspids.